p-Terphenyls From Aspergillus sp. GZWMJZ-055: Identification, Derivation, Antioxidant and α-Glycosidase Inhibitory Activities - Xu, Yanchao; Wang, Yong; Wu, Dan; He, Wenwen; Wang, Liping; Zhu, Weiming (Frontiers in Microbiology, 2021)
One new (1) and fifteen known (2–16) p-terphenyls were isolated from a solid culture of the endophytic fungus Aspergillus sp. GZWMJZ-055 by adding the leaves of its host Eucommia ulmoides. Furthermore, nine p-terphenyls (17–25) were synthesized from the main compounds (5–7), among which derivatives 18, 19, 21, 22 and 25 are new p-terphenyls. Compounds 15 and 16 were also respectively synthesized from compounds 6 and 7 by oxidative cyclization of air in the presence of silica gel. These p-terphenyls especially those with 4,2',4''-trihydroxy (4–7, 20, 21) or 4, 4''-dihydroxy-1,2,1',2'-furan (15, 16) substituted nucleus, exhibited significant antioxidant and α-glucosidase inhibitory activities and lower cytotoxicity to caco-2 cells. The results indicated their potential use as a lead compound or a dietary supplement for treating or preventing the diabetes.